Effect of annealing temperature on the optoelectronic properties and structure of NiO films - Li, Ming-Chen; Dai, Ming-Jiang; Lin, Song-Sheng; Chen, Sheng-Chi; Xu, Jing; Liu, Xiu-Lan; Wu, En-Hui; Ding, An-Ning; Gong, Jian-Hong; Sun, Hui (Ceramics international, 2022)
Nickel oxide (NiO) is a typical transparent conductive oxide with intrinsic p-type conductivity. In this study, NiO thin films were prepared by magnetron sputtering and then subject to rapid thermal annealing (RTA, 50–450 °C) under an ambient atmosphere. The experimental results show that RTA critically affects the optoelectronic properties and crystallinity of NiO films. RTA affects the optoelectronic properties of the films by changing their lattice constants and the formation energy of various defects, and an appropriate annealing temperature is important for obtaining NiO films with ideal optoelectronic properties. The NiO film annealed at 350 °C exhibited the optimal optoelectronic performance, with an enhanced figure of merit (average visible light transmittance of 45% and room temperature resistivity of 384.5 Ω·cm) that is nearly three orders of magnitude higher than that of the films annealed at other temperatures.